Large dentigerous cysts of the mandible in a 46-year-old patient - a case report - Rafał Stelmach; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2017)
The article presents the clinical picture and surgical treatment of large dentigerous cyst associated with impacted tooth in a 46-year-old patient.